IN VITRO SHOOT PROLIFERATION OF STRAWBERRY USING STEM PLANTLET EXPLANT DERIVED FROM MERISTEM CULTURE - Ahmad Syahrian Siregar (Widyariset, 2013)
The fruit of strawberry contain phenolic compounds of vitamin C, B1, and B2 which is beneficial for health The successful of strawberry micropropagation depending on the ability of explants to produce large number of plantlets in short time. In order to increase the number of plantlets by organogenesis the use of plantlet stems as explants need to be optimized. The aim of this research was to investigate the potential of stem plantlet explants on the shoot proliferation of strawberry using 8 medium treatments. Research was conducted in the Plant Breeding Laboratory at Citrus Research Centre and Subtropical Fruit Indonesia, started from February to September 2011. The results showed that explant from stem of plantlet from meristem culture of strawberry could be used as initial material to proliferate strawberry plantlet. High number of plantlet (5.73) was produced on MS medium containing combination of plant growth regulator BAP and NAA at concentration of 0.5 mg/l and 0.025 mg/, respectively.